Dora Maar : Paris in the time of Man Ray, Jean Cocteau, and Picasso - Baring, Louise (Rizzoli Interntaional Publications, Inc., 2017)
An exquisite volume on the beautiful, talented and mysterious Dora Maar, showcasing her Surrealist photography, her life with Pablo Picasso and her friendships with Surrealists in 1930s Paris. Highly regarded as a Surrealist photographer in the 1930s, Dora Maar was a fellow student with Henri Cartier-Bresson and friends with Brassai, Man Ray, Jean Cocteau and Andre Breton, the charismatic leader of the Surrealists. When Maar met Picasso in the mid-1930s, she became the most influential of his many muses, inspiring much of what is considered to be his best work. But during the ten years they were together, she abandoned her career as an acclaimed professional photographer and instead photographed Picasso, including her famous series of him painting Guernica. While Maar was considered an influential Surrealist photographer, most of her work vanished from the public eye once she stopped creating it in the late 1930s. Now, this volume restores her photographs to their place in history, featuring a treasure trove of incredible and never-before-published images. An important look at Surrealist photography, "Dora Maar" is also beautifully illustrated with photographs celebrating Maar's friendships with leading artists and intellectuals of the day, such as Georges Bataille (Maar's former lover), glamorous Nusch Eluard and her husband, the poet Paul Eluard and arts patron and hostess Marie-Laure de Noailles, evoking the atmosphere of 1930s and 40s artistic Paris.